Steganografi Gambar Menggunakan Least Significant Bit Random Placement Untuk Perlindungan Hak Cipta Manuskrip Lontar Bali Berbasis Android (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2023)
The Balinese lontar manuscripts are a valuable ancestral cultural heritage of the Balinese people because they contain ancient knowledge and historical records. Along with the development of ejection age, the material from ejection manuscripts is very vulnerable to damage. This damage can result in loss of information on the ejection, but this can be minimized by digitizing it. At this time if there are many types of lontar manuscripts that are digitized, it will be difficult to find proof of ownership. So, the authors conducted research on creating a copyright protection system for Balinese lontar manuscripts by inserting proof of ownership. The method used for insertion is the LSB method with ChaCha20 as additional security and random key generation. The research was successfully carried out based on the results of testing the computational process on the imperceptibility criterion that there was no difference between the stego image and the original image, then on fidelity got the MSE value of 0.00143 and PSNR 76.56 dB, the results of the recovery criteria stated that the inserted embedded image could be extracted with an average the average time is 20.629 seconds, and on the robustness criterion, the results with the embedded image cannot be extracted because it is not resistant to the processing of the stego image. Another measure of success based on software testing using black box testing is to find that the functional application works well and there are no problematic features and the UAT results get very good ratings from respondents with an average weighting value of 89.2%.